VOICE SYSTEMS IN MANGGARAI: HOW SEMANTIC ROLES BEHAVE IN THE CLAUSES - Salahuddin Salahuddin (Universitas Negeri Makassar, 2023)
This research evaluates Klamer's statement that says several languages in the Lesser Sunda Islands (and some languages in Sulawesi) do not have passive constructions. Therefore, this study aims to prove whether the Manggarai language has passive construction forms with different semantic roles. The data used in this study are clauses in the Manggarai language that contain five semantic role arguments: actor, patient, benefactive, instrumental, and locative. This is done by examining the semantic role argument to be positioned as the subject. The results show that the Manggarai language is indeed a language that has two voices, which means that active and passive constructions exist. However, Manggarai does not experience morphological changes in the verbs but is marked by the emergence of prepositions when changed into passive constructions. In the Kempo dialect of the Manggarai language, the preposition le ‘by’ not only introduces actors in passive constructions but also serves to introduce instrumental roles in active sentences. The preposition latang 'for' introduces a benefactive argument in both active and passive constructions. Preposition one ‘in/on’ serves to introduce a locative argument in active and passive clauses.